FORMULASI HUKUM DAN KARAKTERISTIK FIQIH - Faiz Zainuddin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
Jurisprudence is a legal formulation in which photographing the behaviorof someone who in this case is a Muslim. The existence of fiqh here is nota stagnant law but very flexible or flexible, given the needs and behaviorof the community and social problems in reality continue to experiencevery rapid development. So from this jurisprudence is needed toparticipate in discussing activities that did not occur at the time of theProphet, therefore with the characteristics of fiqh that is flexible anduniversal can answer all problems in the community. Of course it stillcomes from the Koran and Hadith. This research uses explanatoryresearch by applying a qualitative approach. While the analysis ofresearch results used is content analysis. The results of this study, fiqhhas special characteristics so that it can be used as a foothold orparadigm when formulating formal laws, including: perfect, elastic,systematic, universal and tabbudi and taaqquli.